O Som automotivo: patrimonialização, política e mercado - MORAIS, Vanessa Malheiro (Universidade Federal do Pará, 2024)
This research investigates the Belém/PA town hall request to patrimonialize automotive sound, in special the stakeholders behaviours, and assess the valorisation relationships regarding imaterial cultural assets. Through its development, the study presents the Automotive Sound cultural arena, its practices, production, social representation, which deepens the relationships among culture and modern consumption. Field data related to culture, identity and cultural assets were collected in the cities of Belém (PA), Imperatriz (MA), Chapecó (RS) and Osasco (SP). Field work made use of interviews, direct observation, bibliography efforts including internet and social media, newspapers, participation on cultural events (get togethers, meetings, championships); it also included Automobile exposition at Pará Federal University (2018) and the establishment of a virtual and in person interaction network based on WhatsApp. The study allowed the reflection of behaviours and tools adopted by the state seal for the recognition of socially established cultural values and of interests throughout the patrimonial process where historical subjects - through a national practice and policy - leads to a disorder in the patrimony development process. It was observed the establishment of sound cultural expressions in the modern society, based on a political-cultural imaginary and on a hybrid mass culture with diversified lifestyles.